Financial development and affordability of public private partnerships (PPPs): implication for Uganda's infrastructural development plans - Kamara, Edgar (My University, 2016)
This thesis addresses affordability of private financing for infrastructure in the context limited public sources of funding and a low level development of Uganda’s financial sector. The thesis addresses the factors that influence the cost of private financing of public infrastructure; the influence of the level of development of domestic financial markets in the determination of private financing costs of infrastructure projects; the private sector options feasible for financing Uganda’s infrastructure development and the scope for public sector interventions to reduce the cost of private finance in infrastructure. The research project was undertaken between June 2015 and March 2016.The research methodology was mainly library based and qualitative in nature. However, the approach was dual in nature since both existing sources of information and primary data were used. The study has established that in the face of limited public funding and a deficit in infrastructure development expenditure, private financing for public infrastructure is indispensable. However, it is relatively more costly, with good reason. However, there is scope for the public sector to affect favorably the cost of private financing for infrastructure. In particular, steps to address regulatory, political and country risk are critical. Equally important are measures to address macroeconomic instability and strengthen balance of payment positions as well as reforms to widen and deepen the financial sector. In addition, optimizing project selection and preparation as well as a establishing a credible pipeline of infrastructure projects coupled with suitable financing plans can positively impact the cost of private financing for infrastructure.
Thesis submitted in partial fulfillment of the requirements for the degree of Master of Management in Finance and Investment Wits Business School University of the Witwatersrand, Johannesburg, South Africa October 2016
Keywords: Infrastructure (Economics)--Uganda--Finance; Economic development projects--Uganda; Public-private sector cooperation--Uganda